Household Inequality, Welfare, and the Setting of Trade Policy - Joseph Francois; Hugo Rojas-Romagosa (Tinbergen Institute, 2004)
We analyze general equilibrium relationships between trade policy and the household distribution of income, decomposing social welfare into real income level and variance components through Gini and Atkinson indexes. We embed these inequality-adjusted social welfare functions in a general equilibrium structure mapping from tariff protection to household inequality. This yields predictions regarding the linkages between trade protection, country characteristics and inequality in Heckscher-Ohlin and Ricardo-Viner frameworks. In addition, we can separate the efficiency and equity effects of tariffs on welfare. We then examine endogenous tariff formation when policy makers care about both equity and special interests.
Keywords: F13; O15; D31; D72; 330; trade policy; household distribution of income; Atkinson index; Gini index; endogenous tariffs; tariffs and equity; Haushaltseinkommen; Einkommensverteilung; Außenwirtschaftspolitik; Wohlfahrtsanalyse; Gini-Koeffizient; Wohlfahrtstheorie; Theorie